Insight Strategis Efisiensi Operasional dan Dinamika Inflasi terhadap Profitabilitas Bank di Indonesia (2019–2024) - Akhmad Ghozali; Rahma Febrianti (Jurnal Ecoment Global, 2026)
Objective: This study aims to analyze the effect of operational efficiency, proxied by the Cost to Income Ratio (CIR) and Operating Expenses to Operating Income (BOPO), as well as inflation, on bank profitability in Indonesia during the 2019–2024 period. Design/Methodology/Approach: This study employed a quantitative approach with a causal research design. The sample consisted of 33 banking companies listed on the Indonesia Stock Exchange and selected using a purposive sampling technique. Secondary data were obtained from companies’ annual reports and relevant official publications. Data analysis was conducted using panel data regression to examine the effects of CIR, BOPO, and inflation on Return on Equity (ROE). Findings: The results indicate that BOPO has a negative and significant effect on ROE, whereas CIR has a negative but insignificant effect. Inflation demonstrates a positive but insignificant effect on bank profitability. These findings suggest that operational cost efficiency plays a more dominant role in determining profitability compared to external macroeconomic factors. Originality/Value: The originality of this study lies in the simultaneous examination of CIR, BOPO, and inflation on bank profitability using panel data covering the 2019–2024 period. This study highlights the importance of operational efficiency in improving banking profitability amid economic uncertainty and digital disruption. Practical/Policy Implications: This study provides practical implications for banking management to prioritize operational cost efficiency in order to enhance profitability. The findings may also serve as a consideration for regulators in strengthening the internal efficiency of the banking sector in Indonesia.